Pooling of Samples for SARS-CoV-2 Detection Using a Rapid Antigen Test - Salcedo, Nol; Harmon, Alexander; Herrera, Bobby Brooke (Frontiers in Tropical Diseases, 2021)
While molecular assays, such as reverse-transcription polymerase chain reaction (RT-PCR), have been widely used throughout the coronavirus disease 2019 (COVID-19) pandemic, the technique is costly and resource intensive. As a means to reduce costs and increase diagnostic efficiency, pooled testing using RT-PCR has been implemented. However, pooling samples for antigen testing has not been evaluated. Here, we propose a proof-of-concept pooling strategy for antigen testing that would significantly expand SARS-CoV-2 surveillance, especially for low-to-middle income countries, schools, and workplaces. Our laboratory-based testing demonstrates that combining of up to 20 nasal swab specimens per pool can expand surveillance with antigen tests, even if a pool contains only one positive sample.